Development and morphology of the fruit and seed of the hemiparasite genus Jodina (Cervantesiaceae) - Luna, María Luján (2017)
The monotypic genus Jodina is endemic to central and southeastern South America, common in forests and scrubland environments. The fruit type in Jodina is controversial since it has been described at different stages of development. The main objective of this work was to analyze the morphology of the fruit of J. rhombifolia during its maturation to attain a consensus about its type. Also characteristics of seed development and anatomy were analyzed in detail. Material was processed according to conventional techniques for LM and SEM studies. The fruit of J. rhombifolia is a pseudodrupe since the ovary is half-inferior; the fleshy layer of the pericarp is constituted by an increase of the nectary disk whereas the stony layer is represented by the mesocarp. Participation of the nectary disk as part of the fruit wall has not been mentioned previously. The seed is "naked" -the integument disintegrates during development- and the resulting structure is a pyrene. The interpretations made by other authors on the fruit of Jodina are also discussed.